Emerging Markets Instability : Do Sovereign Ratings Affect Country Risk and Stock Returns? - Kaminsky, Graciela (World Bank, 2013)
Financial market instability has been the focus of attention of both academic and policy circles. Rating agencies have been under particular scrutiny lately as promoters of financial excesses, upgrading countries in good times and downgrading them in bad times. Using a panel of emerging economies, this paper examines whether sovereign ratings affect financial markets. We find that changes in sovereign ratings have an impact on country risk and stock returns. We also find that these changes are transmitted across countries, with neighbor-country effects being more significant. Rating upgrades (downgrades) tend to occur following market rallies (downturns). Countries with more vulnerable economies, as measured by low ratings, are more sensitive to changes in U.S. interest rates.